Stability of a Dynamic Input-Output System - Jorgenson, Dale W. (Review of Economic Studies, 1961)
Stability of a Dynamic Input-Output System Get access Dale W. Jorgenson Dale W. Jorgenson Berkeley, California Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 28, Issue 2, February 1961, Pages 105–116, https://doi.org/10.2307/2295708 Published: 01 February 1961